Pattern-Based Augmented Reality Authoring Using Different Degrees of Immersion: A Learning Nugget Approach - Rau, Linda; Döring, Dagny C.; Horst, Robin; Dörner, Ralf (Frontiers in Virtual Reality, 2022)
Creating Augmented Reality (AR) applications can be an arduous process. With most current authoring tools, authors must complete multiple authoring steps in a time-consuming process before they can try their AR application and get a first impression of it. Especially for laypersons, complex workflows set a high barrier to getting started with creating AR applications. This work presents a novel authoring approach for creating mobile AR applications. Our idea is to provide authors with small, ready-to-use AR applications that can be executed and tested directly as a starting point. Authors can then focus on customizing these AR applications to their needs without programming knowledge. We propose to use patterns from application domains to further facilitate the authoring process. Our idea is based on the learning nugget approach from the educational sciences, where a nugget is a small and self-contained learning unit. We transfer this approach to the field of AR authoring and introduce an AR nugget authoring tool. The authoring tool provides pattern-based self-contained AR applications, called AR nuggets. AR nuggets use simple geometric objects to give authors an impression of the AR application. By replacing these objects and further adaptions, authors can realize their AR applications. Our authoring tool draws from non-immersive desktop computers and AR devices. It synchronizes all changes to an AR nugget both to an AR device and a non-immersive device. This enables authors to use both devices, e.g., a desktop computer to type text and an AR device to place virtual objects in the 3D environment. We evaluate our proposed authoring approach and tool in a user study with 48 participants. Our users installed the AR nugget authoring tool on their own devices, worked with it for three weeks, and filled out a questionnaire. They were able to create AR applications and found the AR nugget approach supportive. The users mainly used the desktop computer for the authoring tasks but found the synchronization to the AR device helpful to experience the AR nuggets at any time. However, the users had difficulties with some interactions and rated the AR nugget authoring tool in a neutral field.